PENGARUH KUALITAS LAYANAN, CITRA BANK DAN LOKASI TERHADAP KEPUASAN NASABAH (Studi pada Nasabah Tabungan Tamades PD. BPR BKK Demak Cabang Sayung) - Nurul Khotimah, 15.05.51.0323; Soliha, Euis (Students' Journal of Economic and Management, 2019)
This study aims to test the effect of service quality, bank image, and location on customer satisfaction. This research conducted in PD. BPR BKK Demak Cabang Sayung. The analysis tool used is multiple regression, as for testing the hypothesis using the t test. Data collection through questionnaires with measurements using a Likert scale 5 (five) without alternative answers. The sampling technique is done on a non probability sampling basis and this sampling method uses purposive sampling.The number of samples in this study were 100 customers saving Tamades PD. BPR BKK Demak Branch Sayung. In this study the instrument test used a validity test which showed the results of the KMO value> 0.5 and the value of the loading factor> 0.4 so that all the indicator variables used were declared valid and feasible for research and reliability testing which showed the results of cronbach's alpha> 0, 70 so that it can be said to be reliable. The results of the research show that service quality has no effect to customer satisfaction, the bank's image has a positive and significant effect to customer satisfaction, and location has a positive and significant effect to customer satisfaction.